Gold Nanoparticles Supported on a Layered Double Hydroxide as Efficient Catalysts for the One‐Pot Synthesis of Flavones. Issue 45 (14th September 2015) - Yatabe, Takafumi; Jin, Xiongjie; Yamaguchi, Kazuya; Mizuno, Noritaka
Abstract: Flavones are a class of natural products with diverse biological activities and have frequently been synthesized by step‐by‐step procedures using stoichiometric amounts of reagents. Herein, a catalytic one‐pot procedure for the synthesis of flavone and its derivatives is developed. In the presence of gold nanoparticles supported on a Mg‐Al layered double hydroxide (Au/LDH), various kinds of flavones can be synthesized starting from 2′‐hydroxyacetophenones and benzaldehydes (or benzyl alcohols). The present one‐pot procedure consists of a sequence of several reactions, and Au/LDH can catalyze all these different types of reactions. The catalysis is shown to be truly heterogeneous, and Au/LDH can be readily recovered and reused. Abstract : Go for gold : In the presence of gold nanoparticles supported on a Mg‐Al layered double hydroxide (Au/LDH), various flavones were obtained from the corresponding 2′‐hydroxyacetophenones and benzaldehydes (or benzyl alcohols). All three (four) steps of this one‐pot process are catalyzed by Au/LDH in a truly heterogeneous fashion.